2017
DOI: 10.1021/acs.langmuir.6b03877
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soot on NOx Adsorption over Cu-Modified Hydrotalcite-Derived Lean NOx Trap Catalyst

Abstract: The impact of soot on NO adsorption was studied over a Cu-modified hydrotalcite-derived lean NO trap catalyst in a NO + O atmosphere. Powder X-ray diffraction, scanning electron microscopy, Raman scattering spectroscopy, and X-ray photoelectron spectroscopy were used to characterize the surface properties of the pure catalyst and the soot/catalyst mixture. The adsorbed NO species on the samples were evaluated by in situ diffuse reflectance Fourier transform spectroscopy. The soot coverage decreases the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…67 The vibration band at 1623 cm –1 corresponding to gaseous or weakly adsorbed NO 2 . 68,69 When the temperature is higher than 300 °C, the peaks of the nitrate species disappear in the IR spectra due to their decomposition at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…67 The vibration band at 1623 cm –1 corresponding to gaseous or weakly adsorbed NO 2 . 68,69 When the temperature is higher than 300 °C, the peaks of the nitrate species disappear in the IR spectra due to their decomposition at high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…67 The vibration band at 1623 cm -1 corresponding to gaseous or weakly adsorbed NO 2 . 68,69 When the temperature is higher than 300 °C, the peaks of the nitrate species disappear in the IR spectra due to their decomposition at high temperatures. Based on the above analysis, the possible reaction mechanism for soot combustion on the developed catalysts is proposed, and the corresponding scheme is shown in Fig.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…This is well documented in the literature. 54,55 Thus, this inhibition effect was simulated in this study over the Pd/CeZr/ Al 2 O 3 sample using the reaction expressions and kinetic parameters estimated above, with the purpose of understanding the kinetic processes taking place in the presence of soot over the whole range of operating conditions. Compared to soot-free experiments, the feed temperature was limited between 125 and 300 °C to prevent the soot oxidation, whereas λ-values were kept the same, ranging from 0.85 to 1.15.…”
Section: Resultsmentioning
confidence: 99%
“…This degradation of the TWC activity is probably related to the mass transfer resistance caused by the soot. The soot deposition limits the diffusion of species toward the active sites, resulting in a reduced performance compared to the soot-free samples. …”
Section: Resultsmentioning
confidence: 99%
“…Their results indicated that the presence of soot considerably reduced the formation or stability of ammonium nitrates, leading to higher NO x conversion at low temperatures during fast SCR conditions. On the contrary, Li et al 16 examined the NO x adsorption on a lean NO x trap (LNT) catalyst in the absence and presence of soot. They concluded that the soot trapped physically covered the catalyst surface, causing a masking effect by reducing the number of available NO x adsorption sites.…”
Section: Introductionmentioning
confidence: 99%